The Relationship between Communication in the Family and the Development of Speech in Children Aged 5-6 Years in RW 03 Patenggangan - Niken Alianda; Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
This research is motivated by the low language skills of children. This is evidenced by the number of children who cannot provide answers to complex and clear questions, children are not able to communicate in simple and easy-to-understand sentences, suspected of lack of communication in the family. This study aims to: 1) see the picture of communication in the family. 2) Look at the picture of the language development of children aged 5-6 years. 3) Seeing the relationship of family communication with language development in children aged 5-6 years. The method used in this research is a correlational type quantitative approach. The population in this study are mothers who have children aged 5-6 years in RW 03 Air Tawar Barat Village as many as 56 people. The sample used by the researcher is cluster random sampling. The data collection technique used is in the form of a questionnaire. The data analysis technique uses the percentage formula and product moment. The results showed: 1) The description of family communication in RW 03 was considered good. 2) The description of the language development of children aged 5-6 years in RW 03 is not good. 3) There is a relationship of communication in the family with the language development of children aged 5-6 years in RW 03. Keyword: Communication, Speech development